The association between chronic rhinosinusitis and the risk of dementia: a longitudinal study - Zhang, Xinyu; Yin, Zhongmin; Luo, Jia; Yang, Runsheng; Wang, Weijing; Zhang, Dongfeng (Frontiers in Aging Neuroscience, 2025)
BackgroundChronic inflammation status could increase the risk of dementia, and chronic rhinosinusitis (CRS) could cause chronic inflammation status. Therefore, CRS may be associated with dementia. The aim of our study was to investigate the association between CRS and the risk of dementia in the UK Biobank (UKB) cohort.Materials and methodsA total of 3,64,945 participants were included in this cohort study. CRS information was obtained from the first occurrence date of CRS (Field 131,468) at baseline. A Cox regression model and mediation analysis were performed to measure the association between CRS and dementia.ResultsChronic rhinosinusitis was significantly associated with an increased risk of Alzheimer’s disease (AD) (hazard ratio [HR]: 1.33, 95% CI: 1.04–1.71) but was not associated with the risk of all-cause dementia (hazard ratio [HR]: 1.04, 95% CI: 0.86–1.26) or vascular dementia (VD) (hazard ratio [HR]: 0.65, 95% CI: 0.40–1.07). The male participants, individuals with hypertension, former smokers, participants with less than a college-level education, and participants with a medium-level polygenic risk score for Alzheimer’s disease (PRS-AD) were more susceptible to AD. Mediation analysis using the comprehensive inflammatory index showed that the systemic immune-inflammation index (SII) could explain 0.0042 of this association.ConclusionChronic rhinosinusitis may be associated with a higher risk of AD, and the association was mediated, in a very small part, by the SII.